2005
DOI: 10.1128/aac.49.12.4903-4910.2005
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Ritonavir-Boosted Tipranavir with Loperamide Does Not Result in Loperamide-Associated Neurologic Side Effects in Healthy Volunteers

Abstract: Loperamide (LOP) is a peripherally acting opioid receptor agonist used for the management of chronic diarrhea through the reduction of gut motility. The lack of central opioid effects is partly due to the efflux activity of the multidrug resistance transporter P-glycoprotein (P-gp) at the blood-brain barrier. The protease inhibitors are substrates for P-gp and have the potential to cause increased LOP levels in the brain. Because protease inhibitors, including tipranavir (TPV), are often associated with diarrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…In contrast to loperamide, the pharmacokinetics of the primary CYP3A4-mediated metabolite, N-desmethylloperamide, were unchanged in the presence of GFJ, which may reflect elimination rate-limited kinetics and/or more rapid distribution into peripheral tissues relative to loperamide (Sklerov et al, 2005). The pharmacokinetics of both loperamide and N-desmethylloperamide in the absence of GFJ were consistent with those reported at an equivalent (16 mg) (Mukwaya et al, 2005) or lower (2-4 mg) (Streel et al, 2005;Niemi et al, 2006) loperamide dose after dose normalization.…”
Section: Discussionsupporting
confidence: 77%
“…In contrast to loperamide, the pharmacokinetics of the primary CYP3A4-mediated metabolite, N-desmethylloperamide, were unchanged in the presence of GFJ, which may reflect elimination rate-limited kinetics and/or more rapid distribution into peripheral tissues relative to loperamide (Sklerov et al, 2005). The pharmacokinetics of both loperamide and N-desmethylloperamide in the absence of GFJ were consistent with those reported at an equivalent (16 mg) (Mukwaya et al, 2005) or lower (2-4 mg) (Streel et al, 2005;Niemi et al, 2006) loperamide dose after dose normalization.…”
Section: Discussionsupporting
confidence: 77%
“…Alternatively, absorption can be reduced via induction of these transporters. Clinically significant Pgp interactions have been reported with the PIs tipranavir/ritonavir and the Pgp substrate loperamide, resulting in a 50% reduction in the area under the curve (AUC) of loperamide (Mukwaya et al, 2005). Dolutegravir (DTG) is a tricyclic carbamoyl pyridone integrase inhibitor that blocks the strand transfer step during the integration of the HIV-1 DNA into the genome of the host cell.…”
Section: Introductionmentioning
confidence: 99%
“…TPV (11) and, to a lesser extent, RTV (7) are substrates for P glycoprotein efflux transport. In a drug interaction study with the P glycoprotein substrate loperamide, TPV exhibited P glycoprotein self-induction capability (11).…”
Section: Discussionmentioning
confidence: 99%
“…TPV (11) and, to a lesser extent, RTV (7) are substrates for P glycoprotein efflux transport. In a drug interaction study with the P glycoprotein substrate loperamide, TPV exhibited P glycoprotein self-induction capability (11). In long-term clinical trials with TPV and RTV, TPV has been shown to significantly reduce systemic RTV exposure (14), presumably due to P glycoprotein efflux transport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation